3D-QSAR and Molecular Docking Study on Maleimide-Based Glycogen Synthase Kinase 3 (GSK-3) Inhibitors as Stimulators of Steroidogenesis. (26th May 2020) - Shiri, Fereshteh; Shahraki, Alireza; Nejati-Yazdinejad, Massoud
Abstract: Glycogen synthase kinase-3 (GSK3) is a potential therapeutic target in bipolar disorder. Here, a three-dimensional quantitative structure–activity relationship (3D-QSAR) namely CoMFA, CoMFA-RF (region focusing), and CoMSIA has been carried out on a series (44 compounds) of GSK3 inhibitors on maleimide-based. The data set was divided into training set (32 compounds) and test set (12 compounds) using Kennard and Stone algorithm. An alignment rule for the training set was defined on the basis of common substructure-based alignment. The all-orientation search (AOS) was used to achieve the best orientation and minimize the effect of initial orientation of the structures. The statistical parameters from the models (CoMFA: q 2  = 0.56, r pred 2 = 0.92, CoMFA-RF: q 2  = 0.70, r pred 2 = 0.91, and CoMSIA: q 2  = 0.60, r pred 2 = 0.83 ) indicate that the data are well fitted and have high predictive ability. Molecular docking was employed to explore the binding mode between these compounds and the receptor, as well as help understand the structure–activity relationship revealed by CoMFA and CoMSIA. The computer-aided design of new compounds as potential GSK-3 inhibitors with the application of defined structural alerts was presented.